A comparison of vitreous and soft endosperm high-lysine and common maize in diets for growing rats and pigs - Gómez G., Guillermo G.; Maner, JH; Flores, Z; Francis, C.A. (1975)
Three experiments with growing rats and two with pigs were carried out to evaluate a vitreous endosperm variety of high-lysine maize and to compare its nutritive value with that of a soft endosperm opaque-2 and a common maize. The results indicate that the vitreous endosperm variety has a significantly lower nutritive value than normal soft endosperm opaque-2 maize when fed to growing rats and a slight but nonsignificant inferiority to soft endosperm opaque-2 maize when fed to growing pigs. Chemical analyses and feeding trials indicate that lysine is the first limiting amino acid in the vitreous endosperm variety as compared to the soft endosperm opaque-2 samples.